O Górgias retórico e o Górgias de Platão - Santos, Claudiano Avelino dos (2008)
This paper intends to show the sophist Gorgias of Leontini s thought (ca. 480-380 B.C.); it emphasizes the Rhetoric and Plato s presentation of this sophist in his dialogue Gorgias. To achieve this purpose. We will see the historical contextualization of Greece in V and IV centuries B.C. and give special attention to the importance of lógos for póleis organization. After, the contrast between orality and literacy is studied, pointing the birth of Rhetoric and the effort of sophists in spreading it. The Gorgias thought will be presented based on the investigation of his main works: On the Nonbeing or On Nature, the Apology of Palamedes, the Encomium on Helen. In the first work, Gorgias shows the weakness of lógos to talk about the Being. In the second, he shows the ambiguity of lógos and in the third the power of speech concatenated and with sense upon listener souls. The Plato s thought about the Sophist of Leontini will be presented based on the dialogue Gorgias. In this play Plato shows Gorgias as a skilful master on Rhetoric and make evident the gape of this activity as practiced in Athens, for it doesn t have knowledge about the themes which talk in the court and assembly: the just and unjust. This works also analyzes the reason why Rhetoric is not a téchne for Plato and its character of mimicry